PEMBELAJARAN PENEMUAN TERBIMBING UNTUK MENINGKATKAN PENALARAN MATEMATIS SISWA PADA MATERI PROGRAM LINEAR - Parida Parida; Toto Nusantara; Abadyo Abadyo (Jurnal Kajian Pembelajaran Matematika, 2020)
This study describes the application of guided discovery which improves students' mathematical reasoning in the Linear Program material. This study uses a qualitative approach with the type of Classroom Action Research (PTK). This PTK is implemented in Class XI TPM 3 SMKN 1 Madiun. The application of guided discovery is carried out in four stages. Introduction and Review, namely the teacher conditions students to be ready to learn by conveying learning objectives, explaining the benefits, and reminding the prerequisite material. The Open Stage, in which the teacher sets the group, then the students observe the examples, ask questions, and write down the characteristics of the concept based on the observations. Convergent Stage, where the teacher presents the problem, then students make assumptions, collect information, perform mathematical manipulation, conclude problem solving, re-examine problem solving, and present the results of the discussion. Closing and application, namely the teacher emphasizes important things, the teacher guides students to make conclusions and reflects, then the students work on the quiz. The results showed an increase in students' mathematical reasoning abilities in solving Linear Program problems. Students also gave positive responses to guided discovery learning.Keywords: guided discovery, mathematical reasoning, Linear Program